2018
DOI: 10.3389/fmicb.2018.01741
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Community of Airborne Bacteria in Response to Cyclical Haze Events During the Fall and Midwinter in Beijing, China

Abstract: Since 2013, severe haze events frequently have occurred in Beijing between October and March, which have created a significant public health threat. Although variations in the chemical composition of these haze events have been studied widely, information pertaining to airborne bacteria in such haze events remains limited. In this study, we characterized the concentration, community structure, and composition of the airborne bacteria in response to nine haze events that occurred between October 1, 2015, and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 57 publications
(107 reference statements)
4
24
0
2
Order By: Relevance
“…The cell concentrations C cell in the atmosphere homogenize aloft due to mixing processes and average to concentrations of ∼ 10 4 m −3 at most locations. However, spatial deviations might be present in particular locations, such as cell concentrations of ∼ 7 × 10 5 to 4 × 10 6 cells m −3 that were found during haze periods in China (Li et al, 2018;Xie et al, 2018) and even…”
Section: Discussion Of Uncertainties In Sba Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell concentrations C cell in the atmosphere homogenize aloft due to mixing processes and average to concentrations of ∼ 10 4 m −3 at most locations. However, spatial deviations might be present in particular locations, such as cell concentrations of ∼ 7 × 10 5 to 4 × 10 6 cells m −3 that were found during haze periods in China (Li et al, 2018;Xie et al, 2018) and even…”
Section: Discussion Of Uncertainties In Sba Formationmentioning
confidence: 99%
“…Near the ground, typical concentrations of total airborne bacteria range from ∼ 10 2 to 10 6 cells m −3 , depending on the emission source (Burrows et al, 2009b) and on temporal, meteorological, or other environmental conditions influencing its propensity to emit particles to the air (Carotenuto et al, 2017;Huffman et al, 2013;Lighthart, 1997;Lighthart and Shaffer, 1995). Atmospheric mixing tends to homoge-B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of environmental particles carry a large number of microorganisms, including many pathogens and opportunistic pathogens [17,18]. Particulate matter is one of the key factors affecting the airborne bacterial concentration and community structure [19,20]. Several studies demonstrated that high-levels of PM2.5/PM10 were related to alterations in the human pharyngeal [21], nasal [22], and intestinal [23] microbiota composition.…”
Section: Background and Rationalementioning
confidence: 99%
“…High concentrations of environmental particles carry a large number of microorganisms, including many pathogens and opportunistic pathogens [10,11]. Particulate matter is one of the key factors affecting the airborne bacterial concentration and community structure [12,13]. Several studies demonstrated that high-levels of PM2.5/PM10 were related to alterations in the human pharyngeal [14], nasal [15], and intestinal [16] microbiota composition.…”
mentioning
confidence: 99%